Association of Child Temperament with Early Childhood Caries - ZOHRA JABIN; SEEMA CHAUDHARY (Journal of Clinical and Diagnostic Research, 2014)
Background: Psychological variable may affect early childhood caries (ECC), but this aspect has not been explored satisfactorily. This study evaluates the child temperament as a risk predictor for ECC. Aim: To find the association of child temperament with ECC. Settings and design: The study is a cross-sectional survey of 1300 school children aged 3 - 6 years from Moradabad city. This survey was conducted during March 2008 to April 2009. The survey assessed the child temperament and analyzed its association with ECC. Materials and Methods: Children were examined for the evidence of caries, using dmft (decayed missing filled teeth) index based on W.H.O standard criteria (1997). Child temperament was assessed on the basis of five factors; namely, Sociability, Emotionality, Energy level, Attentivity and Rhythmicity using Malhotra Temperament Schedule MTS. Statistical Package for Social Sciences (SPSS) was used to analyse the data. Significance was deemed at p≤0.05. Results: Out of 1,300 parents involved in filling questionnaire for assessment of child temperament, 1053 (81%) responded and their children were included in study. No caries were found in 731 (69%), while 322 (31%) had evidence of caries in one or more teeth. Of the five temperament factors, Sociability, Energy score, Attentivity and Rhythmicity significantly associated with ECC levels. No correlation could be established with emotionality. Conclusion: The children with ECC were found less sociable, less energetic, highly distractible and less rhythmic as compared to children without ECC.